Charlotte Lennox’s Path to The Female Quixote: A Journey Along and Across Borders - Guidotti, Francesca (Jan Kochanowski University Press, 2023)
This paper explores the literary odyssey of Charlotte Lennox through the English cultural scene of the eighteenth century, marked by the rise of the novel and by a resurgence of Quixotism. Drawing upon biographical reconstruction, historical context, and textual analysis, it interprets Lennox’s multifaceted figure as that of a “frontier writer”, set on negotiating societal and literary boundaries by developing a transformative approach to gender and genre dynamics. After discussing the writer’s ability to forge alliances and turn perceived weaknesses into strengths, the essay traces her trajectory, from early ventures into poetry to her subsequent engagement in prose fiction. It eventually focuses on her second and most renowned novel, The Female Quixote; or, The Adventures of Arabella (1752), which can be read as a confirmation of the barriers of dominant ideology but also as a thought-provoking critique and a longed-for overcoming of those very barriers. Lennox’s work then sheds light on the ideological complexities of the eighteenth-century English novel, meant as a site of both border-raising and border-crossing.This paper explores the literary odyssey of Charlotte Lennox through the English cultural scene of the eighteenth century, marked by the rise of the novel and by a resurgence of Quixotism. Drawing upon biographical reconstruction, historical context, and textual analysis, it interprets Lennox’s multifaceted figure as that of a “frontier writer”, set on negotiating societal and literary boundaries by developing a transformative approach to gender and genre dynamics. After discussing the writer’s ability to forge alliances and turn perceived weaknesses into strengths, the essay traces her trajectory, from early ventures into poetry to her subsequent engagement in prose fiction. It eventually focuses on her second and most renowned novel, The Female Quixote; or, The Adventures of Arabella (1752), which can be read as a confirmation of the barriers of dominant ideology but also as a thought-provoking critique and a longed-for overcoming of those very barriers. Lennox’s work then sheds light on the ideological complexities of the eighteenth-century English novel, meant as a site of both border-raising and border-crossing.